2022
DOI: 10.3389/fcimb.2022.949505
|View full text |Cite
|
Sign up to set email alerts
|

Application of metagenomic next-generation sequencing in the diagnosis of pulmonary invasive fungal disease

Abstract: BackgroundMetagenomic next-generation sequencing (mNGS) is increasingly being used to detect pathogens directly from clinical specimens. However, the optimal application of mNGS and subsequent result interpretation can be challenging. In addition, studies reporting the use of mNGS for the diagnosis of invasive fungal infections (IFIs) are rare.ObjectiveWe critically evaluated the performance of mNGS in the diagnosis of pulmonary IFIs, by conducting a multicenter retrospective analysis. The methodological stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…According to one report, the sensitivity rate of GM serum samples identifying aspergillosis was 65.71%, and the specificity rate was 78.12%. 8 BAL-GM is a sensitive and specific test for the diagnosis of invasive aspergillosis. 9 The efficiency of BAL-GM for diagnosing aspergillosis was relatively high in one study, with 60–100% sensitivity and 68–100% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…According to one report, the sensitivity rate of GM serum samples identifying aspergillosis was 65.71%, and the specificity rate was 78.12%. 8 BAL-GM is a sensitive and specific test for the diagnosis of invasive aspergillosis. 9 The efficiency of BAL-GM for diagnosing aspergillosis was relatively high in one study, with 60–100% sensitivity and 68–100% specificity.…”
Section: Discussionmentioning
confidence: 99%
“…It is less affected by the use of antibiotics and autoimmune status of patient. 15 At present, many studies have explored the significance [16][17][18][19] Our previous research found that mNGS seems to be more meaningful for the diagnosis of fungal infection. 20 Because mucormycosis is rare, the diagnostic value of mNGS is only reported in cases.…”
Section: Discussionmentioning
confidence: 99%
“…But these manifestations are nonspecific. The median time from symptom appearance to suspected IFD was 4 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Patients' Characteristicsmentioning
confidence: 99%
“…There is no doubt that urine culture is still an independent factor in determining the pathogenic organism but not the most important with positive results scoring approximately 20 in the nomogram, even negligible in certain cases, while NTS score was apparently higher and dominant. Multi-study results consistent with clinical experience showed that culture methods always seem to lag, and the positive rate would be influenced by potential applications of empirical antibiotics therapy (Wang et al, 2022). Gupta suggested that the role of urine culture is to retrospectively confirm and emphasized the definition of "contaminants" and the threshold of bacteriuria required for the diagnosis needed to be re-discussed (Gupta et al, 2017).…”
Section: Figurementioning
confidence: 92%